Triple positive solutions for second-order four-point boundary value problem with sign changing nonlinearities - Dapeng Xie; Yang Liu; Chuanzhi Bai (Electronic Journal of Qualitative Theory of Differential Equations, 2009)
In this paper, we study the existence of triple positive solutions for second-order four-point boundary value problem with sign changing nonlinearities. We first study the associated Green's function and obtain some useful properties. Our main tool is the fixed point theorem due to Avery and Peterson. The results of this paper are new and extent previously known results.